Chromosome distribution of four LTR retrotransposons and 18 S rDNA in coffea eugenioides - Mariana Cansian Sattler; Jéssica Coutinho Silva; Stéfanie Cristina Oliveira; Wellington Ronildo Clarindo (Scientific Reports)
Abstract Repetitive sequences are recognized for their roles in plant genome organization and function. Mobile elements are notable repeatome sequences due to their intrinsic mutagenic potential, which is related to the origin of adaptive novelties. Understanding the genomic organization and dynamics of the repeatome is fundamental to enlighten their role in plant genome evolution. We aimed to map and assemble the first karyogram for a Coffea species with a closer look at mobile elements. Four LTR-retrotransposons (LTR-RTs) and the 18S rDNA of Coffea eugenioides, a diploid progenitor of the allotetraploid Coffea arabica, were unprecedently mapped in prometaphase/metaphase chromosomes and interphase nuclei. The LTR-RTs included three Ty1/Copia (Bianca, TAR and Tork) and one Ty3/Gypsy (Athila) identified based on homology searches. The four LTR-RTs were mainly distributed in a clustered pattern throughout different portions of the 2n = 22 chromosomes. Athila showed the most intense fluorescence signals and co-located with the secondary constriction of chromosome 3. In addition, the 18S rDNA was mapped in the distal portions of the short arms of chromosome pairs 3 and 5. The obstacles related to obtaining high-quality chromosomes from Coffea species have long been hampering the cytogenomics, which associates in silico analysis with the in situ mapping. Thus, we hope that the results presented here enlighten not only the composition, but also the distribution of mobile elements in the C. eugenioides genome, providing background for further cytogenomic investigations regarding Coffea repeatome.